2016
DOI: 10.1111/jnc.13464
|View full text |Cite
|
Sign up to set email alerts
|

Administration of low dose estrogen attenuates gliosis and protects neurons in acute spinal cord injury in rats

Abstract: Spinal cord injury (SCI) is a debilitating condition with neurological deficits and loss of motor function that, depending on the severity, may lead to paralysis. The only treatment currently available is methylprednisolone, which is widely used and renders limited efficacy in SCI. Therefore, other therapeutic agents must be developed. The neuroprotective efficacy of estrogen in SCI was studied with a pre-clinical and pro-translational perspective. Acute SCI was induced in rats that were treated with low doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 75 publications
(145 reference statements)
0
40
0
Order By: Relevance
“…; Samantaray et al . ), further experiments were performed to determine if microgliosis and astrogliosis remained inhibited following chronic SCI (day 42). In the current investigation, rats did not receive estrogen therapy beyond 7 days post‐SCI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Samantaray et al . ), further experiments were performed to determine if microgliosis and astrogliosis remained inhibited following chronic SCI (day 42). In the current investigation, rats did not receive estrogen therapy beyond 7 days post‐SCI.…”
Section: Resultsmentioning
confidence: 99%
“…The attenuation of these destructive pathways by very low doses of estrogen in acute SCI (Samantaray et al . ) suggests its neuroprotective capability in ameliorating dysfunction in long‐term (chronic) SCI as well as estrogen's potential as a therapy in human SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…against secondary SCI, together with neuroregenerative agents (e.g., gangliosides, Rho antagonist, anti-Nogo antibodies, acidic fibroblast growth factor) have been used in SCI (Table I) with mixed outcomes (2839). Recent studies also evaluated the potential beneficial effects of estrogen, which could be a neuroprotective agent in the treatment of SCI and TBI (4043). Using a novel strategy of nanoparticle delivery of estrogen showed promising results with induction of anti-Inflammatory effects after SCI in rats (44).…”
Section: Introductionmentioning
confidence: 99%
“…The development of therapeutic approaches for SCI as of yet still remains a problem to researchers and scientists alike (Raspa et al, ). As such, the sagacity of new therapeutics with maximal capacity to improve sensory and motor function after SCI is of utmost importance (Samantaray et al, ). Several studies using renovate strategies have indicated that damaged axons can be regenerated through the lesion site when given an appropriate environment (Zeng et al, ).…”
Section: Introductionmentioning
confidence: 99%